Identification and antigenic characterization of virulence-associated, plasmid-coded proteins of Shigella spp. and enteroinvasive Escherichia coli. - Hale, T L (1985)
Seven plasmid-coded polypeptides, designated a through g, were identified by two-dimensional nonequilibrium pH gradient electrophoresis of radiolabeled extracts from minicells of virulent Shigella flexneri serotypes 2a and 5 and enteroinvasive Escherichia coli O143. These polypeptides were deemed to be products of 140-megadalton (MDa) virulence-associated plasmids because they were not synthesized in minicells which were not harboring a 140-MDa plasmid or in minicells which were carrying an F lac plasmid of the same incompatibility group. Synthesis of these polypeptides was repressed in minicells incubated at 30 degrees C and in minicells isolated from a noninvasive opaque colonial variant, even though these strains harbored a 140-MDa plasmid. Enriched fractions of polypeptides b, c, and d were obtained from S. flexneri serotype 5 by preparative isoelectric focusing, and polyclonal rabbit antisera recognizing each polypeptide were raised. These antisera were able to detect cross-reacting plasmid-coded polypeptide antigens in S. flexneri serotype 3, Shigella sonnei, and enteroinvasive E. coli O143. In addition, Western blots of minicell extracts from S. flexneri serotype 5 or E. coli O143 indicated that plasmid-coded polypeptides a through d were recognized by convalescent antiserum from a monkey infected with S. flexneri serotype 2a.